Proposed interior design scheme of Syaiful Baharim Demi_Courture for Syaiful Baharim at Platinum Mondrian, Jalan Genting Klang, 55330, Setapak Kuala Lumpur / Aizat Amier Irsyad Abdull Ropha - Abdull Ropha, Aizat Amier Irsyad (Faculty of Architecture, Planning and Surveying, 2012)
The plan is a powerful tools in the design process that requires both intellectual and creative rigor. The focus of this article is the methodology of hoe the plan is presented, developed and understood in sophomore interior design studio. The studio’s goal is to give students a foundation of understanding by broadening their knowledge of spatial design through the study of the plan and plan language. The plan is what architects, interior designers and landscape designers use to move people through space, to organize space, and to place objects in space. The article outlines how this material presented through readings, lecture and design projects. The lessons require students to be creative and analytical in developing a plan, to gain visual literacy in understanding a plan and its spaces, and to use plan language in their explanations in studio. Students should learn to think and speak in terms of entry, path and goal. Plan language includes such terms as axis, centering and re-centering, symmetry, focal point, gesturing, reinforcement, in-line, articulation and hierarchy. Students are required to take a letterform and develop an orchestrated spatial walk through the form using plan language, and then they must complete a series of diagrams. Past and present plan types are analyzed and important architects who have contributed to the plan and plan language are discussed (Mackintosh, Wright, Le Corbusier and Scarpa). The plan is the element which most interior designers use to develop space. Therefore, students and educators should have a greater understanding and vocabulary for such an important tool.